The Perspective on Islamic Education is Examined Through The Book "Nahwa Tarbiyah Islamiyah" By Hasan Muhammad Al- Syarqawi - Zaini, Fu’ad; Fahrurrozi, Fahrurrozi; Fattah, Abdul; Thohri, Muhammad (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study aims to analyze the Islamic education perspective of Hasan Muhammad Al-Syarqawi in his book titled 'Nahwa Tarbiyah Islamiyah.' The research method employed is descriptive research with a literature research approach (library research). Data collection involves the analysis of various primary and secondary data relevant to the research theme. The six main characteristics found in Al-Syarqawi's work, namely Manhaj Mutawazin, Fithriyah, Syamil, Waqi`i, Robbaniy, and Manhaj I’jabiy, are the focus of the analysis. As a transformative integrative thinker, Al-Syarqawi has generated innovative concepts in the field of education. These concepts are not only present in his works but have also been successfully applied in both formal and non-formal education contexts. The research results provide valuable insights into the effectiveness of Islamic educational institutions in shaping the character of students through the application of Al-Syarqawi's concepts. The study also identifies that the approach revealed in his book can help Islamic educational institutions become effective in molding the character of students. The implications of this research are that the Islamic education concepts proposed by Al-Syarqawi can serve as a foundation for the development of holistic and functional Islamic education. This supports the formation of a spiritually resilient generation with good intellectual intelligence. The conclusion of this research makes a significant contribution to further development in the field of Islamic education oriented towards character formation and the development of students' potential.